2006
DOI: 10.1118/1.2229428
|View full text |Cite|
|
Sign up to set email alerts
|

Dosimetric characterization of radionuclides for systemic tumor therapy: Influence of particle range, photon emission, and subcellular distribution

Abstract: Various radionuclides have been proposed for systemic tumor therapy. However, in most dosimetric analysis of proposed radionuclides the charged particles are taken into consideration while the potential photons are ignored. The photons will cause undesirable irradiation of normal tissue, and increase the probability of toxicity in, e.g., the bone marrow. The aim of this study was to investigate the dosimetric properties according to particle range, photon emission, and subcellular radionuclide distribution, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 14 publications
2
47
0
3
Order By: Relevance
“…Traditionally, Monte Carlo models are made based on S-values decomposed into self-dose and cross-dose terms. 4,6,9,[11][12][13]42 However, as previously mentioned, the relatively low (10-1000) number of events per cell (N r ), typical of therapeutic regimens, would reduce the value of such average-value approaches in determining TCP since each individual cell's absorbed dose can significantly impact the dosimetric results and a substantial amount of fluctuation in the individual cell absorbed doses can be expected. Spaic et al …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Traditionally, Monte Carlo models are made based on S-values decomposed into self-dose and cross-dose terms. 4,6,9,[11][12][13]42 However, as previously mentioned, the relatively low (10-1000) number of events per cell (N r ), typical of therapeutic regimens, would reduce the value of such average-value approaches in determining TCP since each individual cell's absorbed dose can significantly impact the dosimetric results and a substantial amount of fluctuation in the individual cell absorbed doses can be expected. Spaic et al …”
Section: Discussionmentioning
confidence: 96%
“…The TCP as an important dosimetric end point criterion, arguably the most important criterion, has been extensively discussed, 2,7,13,[37][38][39][40] mostly theoretically, including more recently by Bouchat et al 41 who introduce the concept of SCP or shell control probability as a radial dependent TCP. Traditionally, Monte Carlo models are made based on S-values decomposed into self-dose and cross-dose terms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, the potential to use these characteristics of manufactured radioisotopes to work in synergy rather than in detriment to the treatment goals. Uusijärvi et al 14 proposed dividing radionuclides into groups on the basis of their dosimetric properties, so that this characterization could be taken into account when choosing radionuclides for specific therapeutic applications. Specifically, the authors found differences in the dosage delivered to normal tissue among different types of emitters because of photon contribution in addition to the charged particles they emitted.…”
Section: Impurities and Decay Productsmentioning
confidence: 99%
“…The dosimetric evaluation of therapeutic efficiency of electron emitting radiolanthanides shows that 161 Tb provides better energy transfer in small tumor than 177 Lu because of the high conversion and Auger electrons [12][13]. Accordingly, 161 Tb may be useful as a complement to 177 Lu due to its good tumor-to-normal-tissue mean absorbed dose ratios (TNDs) profile [11].…”
Section: Introductionmentioning
confidence: 99%